A Note on the Validity of Metaphor Universality (The International Journal of Educational Sciences and Arts, 2023)
Metaphor universality has been a topic of long debate among interested researchers. A byproduct of claiming the universality of metaphors is admitting a common human cognition. This cognition is based on different factors external to the cognition itself. In the present study, metaphors from Arabic tweets were analyzed and compared to metaphors in English found in published research. Based on this comparison, it was concluded that metaphors are universal and culturally specific at two different levels. On one level, the shared human anatomy poses universality, and on the other level, factors working against such universality affect the cultural specificity of metaphors. Kövecses (2010b) proposes a list of factors including awareness of context, differential memory, differential concerns and interests, differential cognitive preference and styles, and creativity. Considering languages other than Arabic and English in the comparison can be a promising future research.
Keywords: Metaphor Universality; cultural-specific metaphors; Conceptual Metaphor Theory; Arabic metaphors